2007
DOI: 10.1186/1471-2458-7-212
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and racial/ethnic differentials of C-reactive protein levels: a systematic review of population-based studies

Abstract: BackgroundSocioeconomic and racial/ethnic factors strongly influence cardiovascular disease outcomes and risk factors. C-reactive protein (CRP), a non-specific marker of inflammation, is associated with cardiovascular risk, and knowledge about its distribution in the population may help direct preventive efforts. A systematic review was undertaken to critically assess CRP levels according to socioeconomic and racial/ethnic factors.MethodsMedline was searched through December 2006 for population-based studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
208
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(229 citation statements)
references
References 75 publications
14
208
3
4
Order By: Relevance
“…A recent systematic review of populationbased studies, nearly all from high-income countries, showed higher risk for Africans, South Asians and Hispanics compared to those of European descent, and lower risk for Chinese and Japanese (24). Correct classification of race is complex in a highly miscigenated society such as Brazil but this has not precluded authors from detecting associations between African descent and higher risk of several chronic conditions (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of populationbased studies, nearly all from high-income countries, showed higher risk for Africans, South Asians and Hispanics compared to those of European descent, and lower risk for Chinese and Japanese (24). Correct classification of race is complex in a highly miscigenated society such as Brazil but this has not precluded authors from detecting associations between African descent and higher risk of several chronic conditions (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies on reference values have been performed in wealthy countries (30) where health care systems can afford the CRP test. Also, it has been recognized that demographic factors (including age, gender and race), environmental variables, patient behaviors and traits, such as smoking and infections, contribute to variations in baseline CRP concentrations (31,32). Therefore, in many developing countries, the reference range for CRP is widened due to the presence of chronic parasitic infections, tuberculosis, hepatitis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of CRP are linked to factors such as obesity (Rexrode et al, 2003), and with several dimensions of psychosocial stress, including lack of social integration (Ford et al, 2006) and low SES (Nazmi & Victora, 2007). Few studies involving CRP have been conducted with Latino populations (Midttveit et al, 2010).…”
Section: C-reactive Proteinmentioning
confidence: 99%